1998
DOI: 10.1021/jp9734336
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Dependence of the Hydrodynamical Volume of Dendrimers with a Rubicene Core

Abstract: Four generations of a dendrimer with a fluorescent core consisting of a rubicene moiety are synthesized. The biexponential nature of fluorescence decay in toluene indicates the presence of two emitting conformations. Molecular modeling suggests that a conformation where the dendrons interact with the core is not improbable. The relative weight of the two decay times indicates that the contribution of that conformation in toluene increases as the dendrimer generation increases. In acetone and acetonitrile howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 36 publications
8
73
1
Order By: Relevance
“…De Backer came to similar conclusions using fluorescence depolarization measurements. 19 Both of these studies are in qualitative agreement with the theoretical study of Lescanec and Muthukumar 4 in which the end groups can be found throughout the dendrimer volume, i.e., backfolding occurs. Using rotational-echo double-resonance (REDOR) NMR, Wooley et al were able to show that backfolding occurs in the solid state.…”
Section: Introductionsupporting
confidence: 86%
“…De Backer came to similar conclusions using fluorescence depolarization measurements. 19 Both of these studies are in qualitative agreement with the theoretical study of Lescanec and Muthukumar 4 in which the end groups can be found throughout the dendrimer volume, i.e., backfolding occurs. Using rotational-echo double-resonance (REDOR) NMR, Wooley et al were able to show that backfolding occurs in the solid state.…”
Section: Introductionsupporting
confidence: 86%
“…The CO affinities of the two dendritic iron porphyrins are 3 ± 6 times higher in H 2 O than in dry toluene. Differences in the hydrodynamic volume [49] [50] of the dendrimers could contribute to these changes in affinity. In H 2 O, favorable interactions between the dendritic oligoether branches and the solvent induce a larger hydrodynamic volume, whereas, in dry toluene, the polar branches presumably pack tightly together in order to avoid contact with the apolar solvent.…”
Section: Fe II -12-dimeimmentioning
confidence: 99%
“…It has already been shown in the past that fluorescence depolarization [12,13] is a suitable technique to study the rotational dynamics of fluorescent molecules. There are many parameters that influence this rotational behavior: viscosity, temperature, form of the rotor, interactions between solvent and probe.…”
Section: Introductionmentioning
confidence: 99%